Form, Tense, and Voice of Reporting Verb in Article Text Written by Indonesian Speakers - Rahma Cahyaningrum; Aris Munandar (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2025)
This study examines the characteristics of reporting verb usage in article texts written by Indonesian speakers. This study is qualitative research that focuses on the comparison of the form, tense, and voice of reporting verbs. The data are clauses and sentences from fifty social science articles and fifty science articles published in national journals. The data analysis is based on Hyland’s theory (2002), supported by the theory of tense and voice by Azar (2002) and O’Dwyer (2006). The findings show that the forms of reporting verbs in social science articles are more varied, with around 33 verbs, compared to natural science articles, which amounted to 28. From the findings of these forms, the category classification of reporting verbs in social science leans towards discourse (69.09%), and natural science leans towards research (49.26%). In terms of tense, present simple is the tense that tends to be used in social science. Meanwhile, natural science uses two types of tense: present simple and past simple. Lastly, the voice of the reporting verb in the two disciplines applies active voice. These findings indicate that the characteristics of social research are argumentative, emphasizing the interpretation of ongoing phenomena. On the contrary, the characteristics of social research illustrate that it is experimental, reflecting a verified research process.